2020
DOI: 10.1109/jbhi.2019.2927463
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Neonatal Sepsis Using Features of Heart Rate Variability, Respiratory Characteristics, and ECG-Derived Estimates of Infant Motion

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 40 publications
3
67
0
Order By: Relevance
“…In infants, RMSSD correlated with several outcomes in both the short and the long term: ANS stage of development in the case of prematurity (Hoyer et al, 2009;Lucchini et al, 2016;Aye et al, 2018;Schneider et al, 2018), late-onset sepsis (Joshi et al, 2020), extubation success (Latremouille et al, 2018), recovering after admission in intensive care units (Marsillio et al, 2019), pain behavior (Weissman et al, 2012), short-term neurological development when measured during low blood pressure episodes (Semenova et al, 2018), and later neurological development at 2 years (Dimitrijević et al, 2016). RMSSD showed also to change according to the incubator temperature, thus revealing how infant's HRV changes due to environmental temperature (Stéphan-Blanchard et al, 2013).…”
Section: The Future Perspectives For the Clinical Use Of Hrv In The Nmentioning
confidence: 98%
See 3 more Smart Citations
“…In infants, RMSSD correlated with several outcomes in both the short and the long term: ANS stage of development in the case of prematurity (Hoyer et al, 2009;Lucchini et al, 2016;Aye et al, 2018;Schneider et al, 2018), late-onset sepsis (Joshi et al, 2020), extubation success (Latremouille et al, 2018), recovering after admission in intensive care units (Marsillio et al, 2019), pain behavior (Weissman et al, 2012), short-term neurological development when measured during low blood pressure episodes (Semenova et al, 2018), and later neurological development at 2 years (Dimitrijević et al, 2016). RMSSD showed also to change according to the incubator temperature, thus revealing how infant's HRV changes due to environmental temperature (Stéphan-Blanchard et al, 2013).…”
Section: The Future Perspectives For the Clinical Use Of Hrv In The Nmentioning
confidence: 98%
“…Despite continuous monitoring to assure high care standards, much of this collected information remains unused. This situation is worth noting since integrating these vital signs could improve the predictive power of the NICU monitors and better help reduce infants' mortality (Sullivan et al, 2018;Joshi et al, 2020;Kumar et al, 2020).…”
Section: A Technological Analysis To Efficiently Monitor and Use Hrv mentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is motivated by the fact that the motor activity evolves along with the age of the newborns [14]. Recently, analysis of motion estimated from ECG has been investigated for the detection of late-onset sepsis [15]. Indeed, it has been shown that sepsis is related to lethargy, which can be observed as the absence of motion [16].…”
Section: Introductionmentioning
confidence: 99%